COBIT 5.0: IT Governance Measurement on Reputable Bank in Indonesia - Eric Bagus Saputra Priyono; Wella Wella (Universitas Multimedia Nusantara, 2022)
PT X is required to ensure that IT governance runs well. The maturity level of IT governance needs to be measured to determine what factors each company can improve on. The purpose of this study is to assess the level of capability of PT X, which will be measured using the COBIT 5.0 framework from ISACA, as well as to provide recommendations regarding governance and management of information technology that can build PT X. Measurements were carried out on BAI09 (Manage Assets) and DSS03 (Manage Problems). The results obtained are the BAI09 process and the DSS03 process both stop at Level 4 (Predictable Process), with an average value of 81.30% for the BAI09 process and an average value of 81.84% for the DSS03 process.